Subcutaneous implantable cardioverter defibrillator in patients with arrhythmogenic right ventricular cardiomyopathy: Results from an Italian multicenter registry. (1st April 2019) - Migliore, Federico; Viani, Stefano; Bongiorni, Maria Grazia; Zorzi, Alessandro; Silvetti, Massimo Stefano; Francia, Pietro; D'Onofrio, Antonio; De Franceschi, Pietro; Sala, Simone; Donzelli, Stefano; Ricciardi, Giuseppe; Menardi, Endry; et al.
Abstract: Background: Despite expanding indication of the subcutaneous implantable cardioverter defibrillator (S-ICD) in clinical practice, limited data exists on safety and efficacy of S-ICD in arrhythmogenic right ventricular cardiomyopathy (ARVC) patients. The aim of this multicenter study was to evaluate the safety and efficacy of S-ICD in ARVC patients. Methods: The study population included 44 consecutive patients with definite ARVC diagnosis according to the 2010 ITF criteria (57% male, mean age 37 ± 17 years [range 10–75 years]) who received an S-ICD. Eighteen (41%) patients were implanted for secondary prevention. Results: At implant, all inducible patients (34/44) had conversion of ventricular fibrillation at 65 J. No early complications occurred. During a median follow-up of 12 months (7–19), 3 (6.8%) patients experienced complications requiring surgical revision. No local or systemic device-related infections were observed. Six patients (14%) received a total of 61 appropriate and successful shocks on ventricular arrhythmias. Six (14%) patients experienced 8 inappropriate shocks for oversensing of cardiac signal (4 cases) and non-cardiac signal (4 cases) with one patient requiring device explantation. No patients had the device explanted due to the need for antitachycardia pacing. Conclusions: The study shows that S-ICD provides safe and effective therapy for termination of both induced and spontaneous malignant ventricular tachyarrhythmias with high energy shocks in ARVC patients, but the risk of inappropriate shocks and complications needing surgical revision should be considered. Highlights: Arrhythmogenic right ventricular cardiomyopathy predisposes to ventricular arrhythmias and sudden cardiac death; Transvenous implantable cardioverter defibrillator (T-ICD) is associated with complications requiring surgical revision; Subcutaneous ICD (S-ICD) has entered into the clinical practice and may represent a valid alternative to the T-ICD; Limited data exists on safety and efficacy of S-ICD in ARVC patients; According to our multicentre experience S-ICD is safe and effective in ARVC patients.